VACCINE INNOVATION IN PUBLIC HEALTH: CHALLENGES AND OPPORTUNITIES IN DEVELOPING NATIONS - Dr Ashwini L H; Dr Vinaykumar L H; Dr Hanumanaik L (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Vaccine innovation is essential for improving public health outcomes, particularly in developing nations where access and acceptance vary significantly. This study aims to investigate regional disparities in vaccine accessibility, acceptance, and underlying socio-cultural factors across Sub-Saharan Africa, Southeast Asia, and Latin America, highlighting the challenges and opportunities in these regions. A cross-sectional study design was employed to analyze vaccine access and acceptance levels among populations in these three regions. Data were collected using surveys targeting key demographics and socio-economic indicators, including education level and cultural beliefs. Statistical analyses assessed the correlation between these factors and vaccine uptake rates. Findings reveal notable differences across regions, with Latin America showing higher rates of vaccine accessibility and acceptance due to stronger health infrastructure and education initiatives. In Southeast Asia, cultural beliefs and mistrust in healthcare systems contribute to higher vaccine hesitancy. Educational level was positively correlated with vaccine access across all regions, suggesting that educational interventions may improve vaccination rates. The study underscores the importance of region-specific strategies to enhance vaccine acceptance and accessibility in developing nations. Educational programs and culturally sensitive outreach efforts are crucial for addressing vaccine hesitancy. Future research should focus on longitudinal studies and experimental designs to establish causality and evaluate intervention efficacy, ultimately supporting more tailored public health strategies.